Exploring key factors behind stunting in Indonesian children: Insights from a descriptive study - Anjani, Nur Ilahi; Wardhani, ⁠Hanifiya Samha; Indrawati, Christine; Arbain, Yuniarti; Mertasari, Dwidia; Harap, Inensa Khoirul; Muhashonah, Izzuki (Universitas Muhammadiyah Magelang, 2024)
Stunting remains a significant concern among the Indonesian population, and numerous studies have been conducted to decrease its prevalence. This study aims to analyze the risk factors for stunting in children aged 12 to 59 months. Utilizing a cross-sectional design, the research was conducted in the Sutojayan Health Center Work Area in Blitar. The research population consisted of 396 children aged 12 to 59 months, with a sample size of 60 children. The results indicated that maternal education (P-value = 0.010; OR = 4.4), maternal employment (P-value = 0.025; OR = 5.4), exclusive breastfeeding (P-value = 0.016; OR = 5.8), and environmental sanitation conditions (P-value = 0.027; OR = 3.6) are significantly related to the incidence of stunting. In contrast, children's immunization status did not show a significant relationship (P-value > 0.05). Stunting is influenced by various factors from pregnancy through preschool years, so prevention efforts must begin as early as possible. This includes improving maternal health, promoting breastfeeding, providing nutritious food, preventing infectious diseases, and ensuring a clean environment. The findings of this study encourage healthcare professionals to develop innovative strategies aimed at reducing stunting, particularly in Indonesia. Keywords: Stunting; innovative prevention; community health services; child health; maternal health